The dilemma of the japanese residential street (2018)
The street is an element that is present in all the cities around the world. Through history its role and attributes have change continuously, considering that these vary according to the culture they are in. Several studies have shown how the streets can influence in the life of its users, and how can they adapt according to the needs, but lately cities and streets seem planned for cars and means of transport, leaving behind the importance for pedestrians, and people. The Japanese street diverges from the ones in western cities, the aim of this thesis is to understand the Japanese residential street and its structure as more than a physical element that constructs the city, but also as a social component (place), that carries the task of defining the city by its history and by the different social behaviors, activities and relationships among the users. Different ways of analysis and ways to approach the street are taken into account, taking as cases of study 3 streets in the city of Tokyo. This to get a better idea of the Japanese residential street and all of the components that are related. Concluding with a street-escape proposal for the Japanese cities (that could be applied to any residential area in Tokyo) to develop better cities and public spaces for the community.